Digital Certificate Mapping (Plotting) and Its Legal Impact on Agrarian Reform Acceleration in Kolaka Regency - Ramadhan, Rahmat Fauzi; Alimuddin, Nur Hidayani; Rahman, Irsan (Jurnal Cakrawala Hukum, 2025)
Land disputes and the structural deficiency of Indonesia's land administration system have persisted as fundamental obstacles to the realization of agrarian justice. Digital certificate mapping (plotting), mandated by Ministry of ATR/BPN Circular Number 13/SE/XII/2017, represents a pivotal policy instrument designed to establish spatial legal certainty over registered land rights and to accelerate the national agrarian reform programme. This research examines the implementation of plotting at the Kolaka Regency Land Office, Sulawesi Tenggara, and critically analyses its impact on the acceleration of agrarian reform through a socio-legal approach integrating statutory analysis with primary field data. The findings reveal that plotting, when correctly implemented, contributes substantially to spatial legal certainty by detecting overlapping certificates and producing georeferenced digital parcel records through the SIPETIK system. However, empirical evidence from documented cases including a certificate location mismatch affecting Ny. Harmiani (SHM No. 00614) and an unauthorized plotting case in Okoko Village exposes systemic deficits in technical capacity, institutional accountability, and community engagement that undermine the system's effectiveness for the most vulnerable rights holders. This research concludes that the transformative potential of digital plotting for agrarian reform is contingent upon coordinated investment in licensed cadastral surveyor capacity, institutional transparency mechanisms, and systematic community socialization conditions that remain structurally underdeveloped in the Eastern Indonesian land administration context.